2012
DOI: 10.1148/radiol.12111403
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Median Nerve with MR Neurography by Using Diffusion-Tensor Imaging: Normative and Pathologic Diffusion Values

Abstract: Normative diffusion values for MR neurography of the median nerve with DTI depend on the anatomic location and age but not on sex. Age-specific FA and ADC threshold values might be used to diagnose carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
125
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 40 publications
15
125
0
2
Order By: Relevance
“…Group 3 (n ϭ 6) consisted of postradiation changes without evidence of residual tumor in 6 cases of previously irradiated malignancies, including 3 cases of breast cancer, 1 highgrade sarcoma, 1 case of Hodgkin lymphoma, and 1 case of oral squamous cell carcinoma. Lesion volumes ranged from 1 to 5530 cm 3 The nonparametric Kruskal-Wallis test also showed a statistically significant difference in ADC across the 3 groups, with 2 (df ϭ 2, 23 subjects) ϭ 15.0 and P ϭ .00056. Finally, post hoc nonparametric pair-wise comparisons using the Mann-Whitney U test showed a statistically significant difference in ADC between Groups 1 and 2 (P ϭ .00010) and between Groups 2 and 3 (P ϭ .0012), but no statistically significant difference between Groups 1 and 3 (P ϭ .97).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Group 3 (n ϭ 6) consisted of postradiation changes without evidence of residual tumor in 6 cases of previously irradiated malignancies, including 3 cases of breast cancer, 1 highgrade sarcoma, 1 case of Hodgkin lymphoma, and 1 case of oral squamous cell carcinoma. Lesion volumes ranged from 1 to 5530 cm 3 The nonparametric Kruskal-Wallis test also showed a statistically significant difference in ADC across the 3 groups, with 2 (df ϭ 2, 23 subjects) ϭ 15.0 and P ϭ .00056. Finally, post hoc nonparametric pair-wise comparisons using the Mann-Whitney U test showed a statistically significant difference in ADC between Groups 1 and 2 (P ϭ .00010) and between Groups 2 and 3 (P ϭ .0012), but no statistically significant difference between Groups 1 and 3 (P ϭ .97).…”
Section: Resultsmentioning
confidence: 87%
“…In patients with a classic compression mononeuropathy, such as median nerve compression at the carpal tunnel, the diagnosis can often be made clinically and corroborated by needle electromyography, nerve conduction, and/or imaging studies. [1][2][3][4] For mononeuropathies involving nerves not typically susceptible to compression syndromes, imaging can play an essential role in identifying the lesion and guiding management.…”
mentioning
confidence: 99%
“…Interest is growing in the use of DTI tractography in the assessment of CTS as a result of evidence for its diagnostic value. A correlation between median DTI metrics and electrophysiology for the carpal tunnel nerve has been reported, suggesting a role for DTI in the in vivo assessment of axon and myelin sheath integrity 7,[42][43][44] . According to a meta-analysis published in 2016 that included 316 patients and 293 healthy controls across 12 studies, fractional anisotropy of the median nerve was significantly lower in patients with CTS, and this measure enabled diagnosis of CTS with an overall sensitivity of 82.8% and a specificity of 77.8% 44 .…”
Section: Entrapment Neuropathiesmentioning
confidence: 94%
“…Diffusion tensor imaging (DTI) is another magnetic resonance technique that in the past decade has been introduced to investigations of peripheral nerve disorders. The technique is sensitive to subtle changes of tissue microstructure and enables measure ment of nerve integrity on the basis of quantitative para meters, such as fractional anisotropy, apparent diffusion coefficient, and mean, axial and radial diffusivity 7 . DTI has been used extensively to examine the median nerve at the carpal tunnel and, more recently, to assess the brachial plexus, lumbar plexus and sciatic nerves [8][9][10][11][12][13][14] , although its full diagnostic value remains to be determined.…”
mentioning
confidence: 99%
“…It is in this group of Median nerve has been one of the first PN deeply studied by DTI. Several studies have detailed the technical optimizations for DTN comparing healthy controls with patients with carpal tunnel syndrome (22,61,62). These studies have shown a reduction in FA values in patients with symptoms consistent with carpal tunnel syndrome, suggesting that due to compression, the median nerve loses its physiological anisotropic structure as the extracellular space increases, Also, DTN can detect long-standing neural changes (63).…”
Section: Peripheral Nerve Tunnel Syndromes and Entrapmentsmentioning
confidence: 99%